2002
DOI: 10.1051/0004-6361:20011623
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismology from space: The δ Scuti star θ2 Tauri monitored by the WIRE satellite

Abstract: Abstract. The bright variable star θ2 Tau was monitored with the star camera on the Wide-Field Infrared Explorer satellite. Twelve independent frequencies were detected down to the 0.5 mmag amplitude level. Their reality was investigated by searching for them using two different algorithms and by some internal checks: both procedures strengthened our confidence in the results. All the frequencies are in the range 10.8-14.6 cd −1 . The histogram of the frequency spacings shows that 81% are below 1.8 cd −1 ; rot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…The power spectrum of the WIRE residuals shows a peak at 13.83 cd −1 (see Fig. 6 of Poretti et al 2002) and is therefore probably also present in that data set.…”
Section: Comparison Between the Ground-based And Satellite Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The power spectrum of the WIRE residuals shows a peak at 13.83 cd −1 (see Fig. 6 of Poretti et al 2002) and is therefore probably also present in that data set.…”
Section: Comparison Between the Ground-based And Satellite Resultssupporting
confidence: 54%
“…This remarkable, pioneering study from space led to the discovery of 12 independent frequencies of pulsation down to the 0.5 mmag level (Poretti et al 2002). The satellite data are free of the 1 cd −1 aliasing often present in ground-based data, but include aliasing at the orbital frequency of 15 cd −1 .…”
Section: The 2000 Satellite Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The WIRE data of β Crucis have clearly indicated that more modes are excited than thought up to now from ground-based photometry in this β Cep star (Cuypers et al 2002). This is also the case for the δ Scuti star θ 2 Tauri (Poretti et al 2002). Taking these recent results into account we have selected 10 frequencies out of the pool of observed frequencies for the two classes of stars for our simulation.…”
Section: Interpretation Of the Variabilitymentioning
confidence: 99%
“…The long time base of the data of the latter mission already allowed the discovery of thousands of new periodically variable stars, despite the relatively poor sampling . This led to the publication of the HIPPARCOS catalogue of periodic variable stars (van Leeuwen et al 1997, Grenon et al 1997.…”
Section: Search For New Variablesmentioning
confidence: 99%